Quand un projet de recherche international se fait accompagnateur d’un parcours doctoral : retours d’expériences des actrices - Catherine Adam; Cécile Plaud (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The doctoral program represents a process of training and transformation of individuals. Based on a singular device, the RIIME project (Research on Engineers and Innovation Training in the Maghreb Faced with Environmental Challenges), our research questions the learning process of the doctoral students who are involved in it. RIIME has strong specificities due to its multidisciplinary and international dimension. Our research is based on semi-directive interviews conducted with doctoral students. Two dimensions of the professionalization process structure our results. The first is at the individual level of skills development and shows the contributions in terms of self-confidence, perspective-taking and recognition. The second is at the collective level and highlights the phenomenon of identification, integration and internationalization. This study reveals the benefits and limits of the insertion of young researchers in an international research project.